Relevansi Materi Akhlak dalam Pendidikan Agama Islam terhadap Upaya Pengurangan Perilaku Bullying di Kalangan Peserta Didik - Arief Rohman Arofah (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study examines the relevance of moral (akhlak) material in Islamic Religious Education (PAI) to efforts in reducing bullying among students through a descriptive qualitative approach and library research. The findings show that moral education in PAI provides a foundational framework for fostering empathetic, responsible, and respectful behavior among learners. Core moral values such as honesty, compassion, patience, and self-control directly contribute to the development of an anti-bullying attitude by shaping students’ emotional and social awareness. Furthermore, the internalization of these values through humanistic and interactive learning methods enables students not only to understand moral concepts but also to apply them consistently in daily interactions. The role of PAI teachers as moral exemplars significantly enhances this process, as students often imitate the behaviors demonstrated by their teachers. Additionally, a positive school environment supported by clear rules, cooperative culture, and religious activities strengthens the cultivation of moral character. Therefore, integrating akhlak-based materials in Islamic Religious Education plays a vital role in promoting a safe, inclusive, and bullying-free educational atmosphere